Malnutrition at diagnosis and throughout therapy in pediatric patients with solid tumors: A single‐institution study in a developing country. Issue 11 (7th September 2021) - Sasse, Patricia; Bergmann, Anke; Afonso, Wanelia; Ladas, Elena J.; Ferman, Sima
Abstract: Background: Changesin nutritional status can constitute a risk factor for reduced tolerance and effectiveness of antineoplastic treatment. Knowledge of the nutritional status of pediatric patients is important for implementing interventions to improve outcomes. We aimed to evaluate nutritional status at diagnosis and throughout therapy in pediatric patients with solid tumors. Objectives: To study the prevalence of malnutrition at diagnosis, compare different assessment tools, and examine longitudinal changes in nutritional status during the treatment of pediatric patients with solid tumors in a Brazilian institution. Methods: This prospective single‐center study enrolled patients with solid tumors (age <19 years) from June 2017 to May 2018. Nutritional evaluations were performed at diagnosis and after 3 and 6 months of treatment. z ‐Scores for height for age (H/A) and body mass index for age (BMI/A) were calculated using the Anthro/AnthroPlus software and mid‐upper arm circumference (MUAC) percentile was used for nutritional classification. Results: The prevalence of nutritional status at diagnosis was 29.3% malnourished, 49.5% adequate, and 21.2% overweight/obese. Nutritional status improved during the first 3 months of treatment, with a reduction in the proportion of malnourished patients and an increased number of patients with adequate nutritional status. Conclusions: The two combined indices, BMI/A and MUAC, facilitated the diagnosis of a greater number of patients with solid tumors who had nutritional alterations. A high prevalence of malnutrition was present at diagnosis. Nutritional status improved in the first 3 months of treatment and could be related to the multidisciplinary institutional approach following the diagnosis.